Faktor kemerosotan sektor perdagangan mamluk (872-922H/1468- 1517M): suatu analisis berdasarkan sumber sejarah1 - Wan Kamal Mujani (Institut Kajian Rantau Asia Barat, 2009)
Trade and commerce were among the main sources of income for the Mamluk economy. Because of its geographical and strategic location, the country played an important role as middleman for transactions in and the exchange of western and oriental merchandise, and the Mamluk regime gained considerable revenue from the transit and export trade. While the activities of local and international commerce in Egypt were still in evidence during the period under review, several changes were taking place in this sector. Some ports were in a state of languor and the markets and trading activities there were not so vigorous compared to the period of Turkish Mamluks. In general, trade between the Mamluks and Western and Eastern countries also became less busy. Exports and imports of local as well as foreign goods were not so frequent and extensive as before. This article identifies both internal and external factors as the main causes for the deterioration of commerce in Egypt during the Mamluk period (872-922AH/1468-1517AD). Among the internal factors, for instance, the Mamluk monopolised many activities in trade and even imposed heavy taxes on the local and foreign merchants. This had negative effects on the commercial activities during that time. The disturbances by the Julban (the royal Mamluks) and Bedouins also affected the commercial sector. During this insecure situation, trade and commerce could not develop. Apart from that, Frankish pirates and the blockade by the Portuguese were among the major causes of the deterioration in trade and commerce. The Frankish pirates caused havoc to the Mamluk trade in the Mediterranean Sea and the Portuguese stopped the Mamluk monopoly of the spice trade. At the same time, the constant struggle against these two enemies put an additional strain on the tottering economy of the Mamluk.